2017
DOI: 10.1007/s12076-017-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of size on business net change during crises: a multifactor partitioning analysis of Italian regions during 2007–2010

Abstract: This paper discusses the effects of size on business net change at the local unit level in Italy during the crisis started in 2008. The multifactor partitioning (MFP) approach is proposed for the analysis. The results suggest that units employing 10 to 49 employees benefit from moderating effect due to size, while for micro unitsthose employing less than 10 personsthe crisis is exacerbated by size-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…MFP revises shift‐share analysis, first, by properly computing the effects of different factors through a separation of the effects of variables from the interactions between these variables (Ray et al., 2012; Lamarche et al., 2003). Second, MFP extends shift‐share analysis to cases that involve more than two factors (Bianchi & Biffignandi, 2017; Ray, 1996). Based on the Ray‐Srinath model, computing MFP on the employment growth rate data for each legal form observed within a given period enables its division into five effects (i.e.…”
Section: Sector Region or Legal Form: What Counts Most?mentioning
confidence: 99%
See 1 more Smart Citation
“…MFP revises shift‐share analysis, first, by properly computing the effects of different factors through a separation of the effects of variables from the interactions between these variables (Ray et al., 2012; Lamarche et al., 2003). Second, MFP extends shift‐share analysis to cases that involve more than two factors (Bianchi & Biffignandi, 2017; Ray, 1996). Based on the Ray‐Srinath model, computing MFP on the employment growth rate data for each legal form observed within a given period enables its division into five effects (i.e.…”
Section: Sector Region or Legal Form: What Counts Most?mentioning
confidence: 99%
“…It should be mentioned that some studies (Bianchi & Biffignandi, 2017; Ray, 1996) have shown that the size of businesses may have a significant impact on employment‐level changes. Therefore, sizes should be considered as a fourth dimension affecting overall employment variation.…”
Section: Sector Region or Legal Form: What Counts Most?mentioning
confidence: 99%